Sexual-specific disgust sensitivity mechanisms in homonegativity and transnegativity; the mediating role of right-wing authoritarianism (RWA) (2023)
Disgust specific to sexual stimuli has been thought to be an adaptation that serves purposes of pathogen-avoidance, partner selection and social dominance. While the link between disgust responses and homonegative and transnegative attitudes has been relatively established, it is not yet clear why. Literature using evolutionary psychology perspectives of these phenomena is scarce in areas with substantial LGBT-related violence like Colombia. This research aimed to study the interplay of predispositional (e.g. sociodemographic, reported contact), affective (e.g. disgust sensitivity) and cognitive (e.g. Right-Wing Authoritarian) variables in homonegative and transnegative attitudes of Colombian adults. Participants (N = 272) had a mean age of 26.38 (SD = 9.47), women comprised 72% of the sample and men 28%. Hierarchical regression analyses showed that increased sexual specific disgust sensitivity and greater RWA predicted stronger homonegativity and transnegativity. The relationship between sexual disgust and prejudice was partially mediated by RWA. Findings suggest that sexual disgust sensitivity adaptations in homonegativity and transnegativity may respond to selection pressures that differ from pathogen-avoidance perspectives, and that are associated with maintaining social hierarchy and social dominance. Anti-prejudice initiatives would benefit from targeting emotional responses of sexual disgust, especially within communities and institutions that have historically endorsed conservative and traditional values.